2013
DOI: 10.1371/journal.pone.0076454
|View full text |Cite
|
Sign up to set email alerts
|

North-South Differentiation and a Region of High Diversity in European Wolves (Canis lupus)

Abstract: European wolves (Canis lupus) show population genetic structure in the absence of geographic barriers, and across relatively short distances for this highly mobile species. Additional information on the location of and divergence between population clusters is required, particularly because wolves are currently recolonizing parts of Europe. We evaluated genetic structure in 177 wolves from 11 countries using over 67K single nucleotide polymorphism (SNP) loci. The results supported previous findings of an isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 57 publications
9
87
0
Order By: Relevance
“…Results indicate that the main geographical populations in central and southern Europe are genetically distinct. The Italian and the Iberian wolves were the first ones to cluster separately in both multivariate and Bayesian clustering, confirming Lucchini et al [13], Stronen et al [52], and Pilot et al [16]. Wolves sampled from populations in the eastern countries, and particularily from the Balkan and Carpathian regions show signatures of admixture, supporting previous mtDNA and autosomal SNP findings [16,52].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Results indicate that the main geographical populations in central and southern Europe are genetically distinct. The Italian and the Iberian wolves were the first ones to cluster separately in both multivariate and Bayesian clustering, confirming Lucchini et al [13], Stronen et al [52], and Pilot et al [16]. Wolves sampled from populations in the eastern countries, and particularily from the Balkan and Carpathian regions show signatures of admixture, supporting previous mtDNA and autosomal SNP findings [16,52].…”
Section: Discussionsupporting
confidence: 82%
“…Samples from WBALK, WCARP and WBALT were not used in the simulations because these populations are still in connection one another and also with unsampled wolf populations in eastern Europe [51,52]. …”
Section: Methodsmentioning
confidence: 99%
“…We also used ADMIXTURE to carry out a separate analysis for Eastern European wolves only. We performed this additional analysis because earlier studies suggested population structuring in this region (Pilot et al, 2006;Stronen et al, 2013), which could have remained undetected in the context of strongly differentiated wolf populations from other parts of the world.…”
Section: Genome-wide Diversification In European Wolves M Pilot Et Almentioning
confidence: 99%
“…In Eastern Europe, there are large and interconnected populations (Figure 1), most of which have experienced constant hunting pressures. Cryptic population structure has been observed in Eastern Europe (Pilot et al, 2006;Stronen et al, 2013), but this genetic differentiation is small compared to the differentiation between Eastern Europe and both Italian and Iberian populations. Therefore, herein, we use the term 'Eastern European population' despite the lack of panmixia.…”
Section: Introductionmentioning
confidence: 96%
“…Despite partially recovering from heavy poaching and the use of poisoned baits, wolves in Greece are still threatened by human-caused mortality, limited food availability and on-going habitat destruction and fragmentation (Iliopoulos, 2009). Although belonging genetically to the wider Dinaric-Balkan population (Stronen et al, 2013), genetic structure of a population at the edge of its range, such as the wolf population in Greece, may vary at a smaller, local scale (Yannic et al, 2012) and lower genetic variation may occur after recent population recovery events (Excoffier et al, 2009). The aim of this study was to evaluate the population structure, genetic diversity and population history of wolves in Greece and identify conservation priorities for the species in the country.…”
mentioning
confidence: 99%